2008
DOI: 10.1016/j.jnoncrysol.2008.06.106
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cryomilling on structure of CoFeZrB alloy

Abstract: a b s t r a c t X-ray diffraction experiments indicate that cryomilling of an amorphous CoFeZrB alloy significantly retards mechanically-induced crystallization. After 12 h of milling, the samples consist mostly of an amorphous component and tiny fraction of bcc-Fe. Significant changes are observed on the radial distribution function, suggesting the reordering of atoms within the amorphous phase. Investigation of thermal stability and magnetic properties also indicate that the observed changes upon cryomilling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
(5 reference statements)
1
2
0
Order By: Relevance
“…The amplitude of the first and second feature is lower compared to the third metal-metal feature, due to the low weighting factor of boron [33]. The bond distances observed are in good agreement to literature [13,22,34]. Comparing the amplitude of the metal to non-metal bond population of the Co 43.5 Ta 6.1 B 50.4 and the Co 43.5 Fe 20 Ta 6.1 B 15.8 O 14.8 system it can be observed that the metal to non-metal population of the Co 43.5 Ta 6.1 B 50.4 system is higher.…”
Section: Resultssupporting
confidence: 88%
“…The amplitude of the first and second feature is lower compared to the third metal-metal feature, due to the low weighting factor of boron [33]. The bond distances observed are in good agreement to literature [13,22,34]. Comparing the amplitude of the metal to non-metal bond population of the Co 43.5 Ta 6.1 B 50.4 and the Co 43.5 Fe 20 Ta 6.1 B 15.8 O 14.8 system it can be observed that the metal to non-metal population of the Co 43.5 Ta 6.1 B 50.4 system is higher.…”
Section: Resultssupporting
confidence: 88%
“…NiCoCrAlYSi [163,254] MnBi [255], -MnAlC [256,257], MnAlC/-Fe [258], Carbon doped MnAl [259], Cobalt ferrite [260],-Fe4N [261], BiFeO3 [262]. The change in magnetic properties is mainly due to altering in crystallinity of the materials by cryomilling [263].…”
Section: Hybrid Magnet Materialsmentioning
confidence: 99%
“…There are reports in the literature on magnetic materials being prepared by cryomilling in the nanocrystalline form, such as NiCrAlY [252], NiCoCrAlYSi [163,253] MnBi [254], τ-MnAlC [255,256], MnAlC/α-Fe [257], Carbon doped MnAl [258], Cobalt ferrite [259],γ-Fe 4 N [260], BiFeO 3 [261]. The change in magnetic properties is mainly due to altering in crystallinity of the materials by cryomilling [262]. Similarly, Ni–Nb–Y was cryomilled for catalytic activity and showed higher activity for hydrogen evolution [263].…”
Section: Cryogrinding Of Polymer and Polymer-based Compositesmentioning
confidence: 99%